2011
DOI: 10.1186/1754-9493-5-31
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for avoiding knee pain after intramedullary nailing of tibial shaft fractures

Abstract: BackgroundThe objective of this study is to analyze the proximal tibiofibular joint in patients with knee pain after treatment of tibial shaft fractures with locked intramedullary nail.FindingsThe proximal tibiofibular joint was analyzed in 30 patients, who reported knee pain after tibial nailing, and standard radiograph and computed tomography were performed to examine the proximal third of the tibia. Twenty patients (68.9%) presented the proximal screw crossing the proximal tibiofibular joint and 13 (44.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
11
3
Order By: Relevance
“…13,15 Furthermore, unreamed procedures involving smaller-diameter nails are associated with a lower incidence of anterior knee pain, possibly because of less bone and soft tissue injury. 22 However, the current study failed to demonstrate a relationship between the incidence of anterior knee pain and sex, age, nail diameter, or fracture classification. The surgical approach used during IM nailing also contributes to anterior knee pain.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…13,15 Furthermore, unreamed procedures involving smaller-diameter nails are associated with a lower incidence of anterior knee pain, possibly because of less bone and soft tissue injury. 22 However, the current study failed to demonstrate a relationship between the incidence of anterior knee pain and sex, age, nail diameter, or fracture classification. The surgical approach used during IM nailing also contributes to anterior knee pain.…”
Section: Discussioncontrasting
confidence: 73%
“…24 Although the etiology of anterior knee pain remains unknown, it seems to be multifactorial. 9,[13][14][15][16][17][18][19][20][21][22] Keating et al 7 and Court-Brown et al 8 reported that younger patients tend to be more symptomatic than older patients, likely as a result of being more active. A few studies reported that women also tend to be affected more often than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, a medial longitudinal incision is made, with care being taken not to damage the patellar tendon or its sheath. The patellar tendon, the retropatellar fat pad and paratendinous tissue are retracted and, theoretically there would be no tissue injury [13]. Therefore, it was our belief that by this approach the patellar tendon would be protected from any additional trauma, as much as it is reasonably achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the distance from the tip of the nail to tibial plateau or the anterior border of the tibia was not the only factor contributing to knee pain. Labronici et al [12] performed CT scans on 30 patients treated with interlocking intramedullary nails who had complained of knee pain postoperatively, and the results showed that the proximal interlocking pin entered the tibiofibular joint in 20 of these patients, which may be the iatrogenic cause of knee pain. In addition, Hemigou and Cohen [13] have shown that postoperative knee pain correlated with damage to the internal structure of the knee joint, including the nerves and the fat pad under the patella.…”
Section: Discussionmentioning
confidence: 99%